Encyclopedia of Aesthetics - Kelly, Michael 1762-1826 (Oxford Oxford University Press, 1998)
The Encyclopedia of Aesthetics is the most substantial English-language reference work devoted solely to the exploration of this subject. Featuring more than 600 articles by more than 500 globally recognized art historians, philosophers, and theorists, this encyclopedia provides coverage of historical accounts and critical discussions on the subject. While aesthetics is often thought of as a Western tradition beginning in the 18th century, the roots of an interdisciplinary critical approach to art and culture run far deeper from the Classical era through the Renaissance and up to the present day. From Plato to Heidegger, Romanticism to Post-Modernism, Beauty to Ugliness, this authoritative source provides an even representation of the wide range of competing ideas in the field today. This encyclopedia surveys the full breadth of critical thought on art, culture, and society; it is a comprehensive survey of major concepts, thinkers, and debates about the meaning, uses, and value of all the arts from painting and sculpture to literature, music, theater, dance, television, film, and popular culture. Of special interest are in-depth surveys of Western aesthetics and broad coverage of non-Western traditions and theories of art. The full text of this reference work is available and searchable within Oxford Art Online, and is cross-searchable with other resources
Keywords: Esthetics; Encyclopedia